2010
DOI: 10.1159/000321569
|View full text |Cite
|
Sign up to set email alerts
|

Y-Chromosome Disomy and Trisomy in Scarabaeid and Cerambycid Beetles

Abstract: In a series of about 500 specimens, including 420 males, of karyotyped Polyphaga beetles, 5 males with chromosome Y aneuploidy were detected. One male of each Dicronorrhina derbyana oberthuri (Scarabaeidae), Agapanthia violacea and Morimus funereus (Cerambycidae) were XYY, and 2 probably related and sterile males of Marmylida marginella (Scarabaeidae) were XYYY. These and literature data suggest that Y chromosome aneuploidies are much more frequent in polyphagan beetles than any other group of animals with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Morimus funereus . Published data: description of a disomy Y: 25,XYY (Dutrillaux and Dutrillaux, 2011). The karyotype, similar in specimens from the different localities, does not look different from that of the previous taxa: 24,XY and 11 + Xyp in the males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morimus funereus . Published data: description of a disomy Y: 25,XYY (Dutrillaux and Dutrillaux, 2011). The karyotype, similar in specimens from the different localities, does not look different from that of the previous taxa: 24,XY and 11 + Xyp in the males.…”
Section: Resultsmentioning
confidence: 99%
“…Their morphology recalls that of L. textor Linnaeus, 1758 and also that of species of Dorcadion Dalman, 1817 generally classified into Dorcadionini. Very few cytogenetic studies were performed (Smith and Virkki, 1978;Dutrillaux and Dutrillaux, 2011;Okutaner et al, 2011) and there is neither conclusions about the species status within genera, nor the phylogenetic relationships between genera. In a recent study of CO1 and ITS2 genes, developed on M. asper and M. funereus specimens from Italy, Croatia, Montenegro Slovenia, Turkey and Peloponnese, Solano et al (2013) concluded that their genetic distance is small and compatible with the presence of a single species.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them had XY sex chromosomes, but we found XYY males in about 1% of the specimens analysed [Dutrillaux and Dutrillaux, 2011]. In 24 species from 9 families, the males studied had an X0 sex formula.…”
Section: Resultsmentioning
confidence: 64%
“…It was supposed to be important for a correct segregation of the sex chromosomes at anaphase I, but as suggested by the multiple occurrences of XYY males, it is not unfailing [Dutrillaux and Dutrillaux, 2011]. The occurrence of X0 males is the expected reverse situation caused by the incorrect segregation of the Y.…”
Section: Discussionmentioning
confidence: 99%
“…In other beetles, the rare increases in sex chromosome numbers are most often due to the gain of the Y chromosome. However, the accidental formation of the XYY male sex formulae, as that of X0, is caused by the non-disjunction of the faulty Xyp system of Coleoptera, and not by chromosome fission [27]. Fissions involving the X chromosome during evolution of beetles, as in other animals, seem to be very unusual and not formerly demonstrated.…”
Section: Chromosome Fission In New Caledonian Passalidae: An Exceptio...mentioning
confidence: 96%